Primary Frequency Stability Support of a DFIG in Association With Pitch Angle Control - Si, Xiuli; Wu, Xiaoxin; You, Feng; Yuan, Hongliang; Xu, Yien; Yang, Dejian (Frontiers in Energy Research, 2022)
For an electric power grid that has large penetration levels of variable renewable energy including wind generation and photovoltaics, the system frequency stability is jeopardized, which is manifest in lowering frequency nadir and settling frequency. This paper suggests an enhanced primary frequency response strategy of a doubly-fed induction generator (DFIG) in association with pitch angle control. The DFIG works in de-loaded operation with a certain reserve power via pitch angle control prior to disturbances for frequency regulation. To address this, a function of the pitch angle is employed that decreases the pitch angle with time to slowly feed the active power to the power gird. The simulation results demonstrate the effectiveness and feasibility of the proposed primary frequency response strategy including the settling frequency and frequency nadir.